PENGARUH SOSISALISASI PAJAK BUMI DAN BANGUNAN TERHADAP KEPATUHAN WAJIB PAJAK KOTA BAUBAU - Rais R, Muhammad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
This study aims to determine the effect of land and building tax socialization on taxpayer compliance in the City of Baubau. The data collection methods used were Interview (Interview), questionnaire and observation. The method of analysis of this research is linear regression analysis. Based on the results of research and discussion of the effect of land and building tax (PBB) socialization on taxpayer compliance in Baubau City, it can be concluded that the socialization of Land and Building Tax (PBB) has a positive and significant effect on taxpayer compliance in Baubau City. From the results of simple regression analysis produces a simple regression equation Y = 31.075 + 0.354 X. These results mean that every single point change is influenced by 0.354 socialization. The higher the socialization of Land and Building Tax, the better because it will increase taxpayer compliance in the City of Baubau.